Progressive Muscle Relaxation for Anxiety and Hyperglycemia in Diabetes Mellitus Type 2 Patient: A Case-Study - Himmah, Faiqotul; Nistiandani, Ana; Hakam, Mulia; Setyowati, Sulis (Jurnal Kegawatdaruratan Medis Indonesia, 2024)
Hyperglycemia is the main symptom in patients with diabetes mellitus. One of the risk factors that can increase blood sugar levels in diabetes mellitus (DM) patients is anxiety and stress, as a result of diabetes mellitus sufferers who experience anxiety, their physical condition does not improve, and their blood sugar levels are always high. Progressive muscle relaxation therapy (PMR) is a therapy that aims to focus the patient's attention so that they can differentiate the feelings that occur when the muscles are relaxed or relaxed from when they are contracting so that the patient can manage their body condition against their anxiety. This study aims to analyze the provision of progressive muscle relaxation therapy to control anxiety levels and blood sugar levels in patients with type 2 diabetes mellitus in the Gardena medical ward of Dr. Soebandi Hospital Jember. This research uses descriptive methods in the form of case studies on a patient with Type 2 DM. Therapy was given once a day for 20-30 minutes. Anxiety levels were measured using the DASS questionnaire, and blood sugar measurements were made using a blood sugar stick. After being given PMR therapy for 3 x 24 hours, the patients experienced a decrease in anxiety levels and blood sugar levels. Providing PMR therapy is effective in treating unstable blood glucose levels and anxiety for patient with Type 2 DM.